Biomimetic small exosome with outstanding surgical applications for rapid large-scale wound healing and functional sweat gland restoration. (August 2022) - Chen, Huating; Liu, Yawei; Liu, Yiqiong; Ji, Shuaifei; Xiang, Jiangbing; Li, Yan; Zhou, Laixian; Gao, Huanhuan; Deng, Zihui; Li, Binghui; Sun, Sujing; Cui, Shaoyuan; et al.
Abstract: The realization of coordinated infiltration of dermal and epidermal cell types, and the rapid deposition of extracellular matrix are the prerequisites for improved healing quality of large skin defects. However, presently used materials are limited for wound healing due to the inherent poor histocompatibility, low permeability, poor mechanical property and cytotoxicity. It is challenging to develop new therapeutic agents that enable timely and efficient wound healing and meanwhile there are minimal side effects to avoid chronic wounds, wound adhesions, and large scarring. Herein, we fabricated biomimetic exosomes (EMs) that enriched transforming growth factor β1 (TGF-β1) for the rapid healing of large-scale cutaneous wounds. The EM encapsulation allowed well-managed dosing of the TGF-β1 to effectively promote the wound healing process by endowing epidermal keratinocytes with a migratory feature, enhancing their stem cell properties, and resulting in accelerated in vivo wound re-epithelization. Specifically, the EMs could fast restore the function of sweat glands in a thermally injured mice model. Our work provides a promising strategy for improving the healing speed and healing quality for patients with large wounds. Graphical Abstract: ga1 Highlights: Biomimetic exosomes are developed for the rapid large-scale wound healing. TGF-β1 is in situ induced and enhanced in the exosomes in a mild way. Biomimetic exosomes promoted the restoration of functional sweat glands. This work opens up a new sight in developing cell-free regenerative materials.